An Stomatin, Prohibitin, Flotillin, and HflK/C-Domain Protein Required to Link the Phage-Shock Protein to the Membrane in Bacillus subtilis - Scholz, Abigail Savietto; Baur, Sarah S. M.; Wolf, Diana; Bramkamp, Marc (Frontiers in Microbiology, 2021)
Membrane surveillance and repair is of utmost importance to maintain cellular integrity and allow cellular life. Several systems detect cell envelope stress caused by antimicrobial compounds and abiotic stresses such as solvents, pH-changes and temperature in bacteria. Proteins containing an SPFH-domain, including bacterial flotillins have been shown to be involved in membrane protection and membrane fluidity regulation. Here, we characterize a bacterial SPFH-domain protein, YdjI that is part of a stress induced complex in B. subtilis. We show that YdjI is required to localize the ESCRT-III homolog PspA to the membrane with the help of two membrane integral proteins, YdjG/H. In contrast to classical flotillins, YdjI resides in fluid membrane regions and does not enrich in detergent resistant membrane fractions. However, similarly to FloA and FloT from B. subtilis, deletion of YdjI decreases membrane fluidity. Our data reveal a hardwired connection between phage shock response and SPFH proteins.